The ethical requirement. On Kierkegaard’s doctrine of love - Muñoz Fonnegra, Sergio (Estudios de Filosofía, 2005)
One of the leading concepts in Kierkegaard’s thought is the ethical demand. He introduces it as a corrective against the nihilist tendencies of his times. This article presents the most important aspects of the development of the concept, beginning with Kierkegaard’s critical diagnosis of modernity and his dialectics of both ethical communication and ethico-religious communication. The central thesis is that love, understood as the radical demand made on the individual to overcome selfishness and to help others to be independent, possesses a normative content that encourages the positive development of interpersonal relations.